Experience of Physical Therapy Undergraduates with Psychomotor Interventions in Children in Primary Care (REMUNOM, 2025)
Objective: To report psychomotor interventions in schoolchildren aged 3 to 5 years in primary health care from the perspective of physical therapy students. Methods: A descriptive study in the form of an experience report, based on the activities of an extension project focused on child psychomotricity, carried out in a Municipal Early Childhood Education Center (CMEI) located in the northern region of the city of Teresina, Piauí, from August to December 2024.Results and Discussion: The psychomotor interventions provided significant progress in areas such as fine and gross motor skills, laterality, coordination, and spatial and temporal perception. They also stimulated reasoning, social interaction, and cooperation among the children. The project contributed to the children’s integral development, fostering self-awareness, creativity, and autonomy. Conclusion: Participation in the project enabled physical therapy students to apply their acquired knowledge in practice, while the psychomotor interventions promoted significant improvements in the children, including those with autism spectrum disorder.